PERENCANAAN SISTEM TATA UDARA RUANG OPERASI DI RUMAH SAKIT IBU DAN ANAK PURI BUNDA TABANAN BALI - I Gusti Ngurah Kade Suwiherawan; I Gede Dyana Arjana; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2021)
The Puri Bunda Mother and Child Hospital in Denpasar opened a new branch inTabanan. The operating room is one of the focuses in realizing patient safety-oriented services.The government with PMK No. 24 of 2016 and Technical Guidelines for Hospital Infrastructurefor Air System Installation Systems in 2012 requires operating rooms to meet requirements suchas: room temperature ranges from 20ºC - 24ºC, humidity 40% - 60%, equipped with HEPA filterwith 99.97% efficiency, positive pressure of 15 pascal to the surrounding space, and equippedwith a clean air exchange system. the result research and calculations in planning theoperating room air conditioning system at the Puri Bunda Tabanan Mother and Child Hospitalaccording to the standards obtained a split duct capacity of 60,000 btu / h, a heater of 7KW, aBooster fan of 1900 CFM, a HEPA filter of 120cm x 80cm. 2 units for each room, 42cm x 42cmducting inlet outlet, 20cm x 25cm RAG and FAG ducting, 380 CFM exhaust fan.